The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3389/fphys.2020.00951
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Gene D/I Polymorphism in Relation to Endothelial Function and Endothelial-Released Factors in Chinese Women

Abstract: Many studies have investigated the relationship between angiotensin-converting enzyme (ACE) D/I polymorphism and cardiovascular disease or endothelial dysfunction; however, hardly any of these studies has taken aging or menopause into consideration. Furthermore, despite that many studies have examined the regulatory effects of endothelial-released factors (ERFs) on endothelial function, no study has evaluated the relationship between ERFs and endothelial function with respect to ACE D/I polymorphism and menopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…There appears to be selective targeting of the tissular ACE population linked to endothelial dysfunction by the lipophilic enalapril. This is in accordance with findings correlating vascular ACE inhibition (measured by changes in angiotensin peptide levels) [32] or vascular ACE expression (determined by genetic polymorphism) [33] with endothelial function. Moreover, the inhibition of ACE (and type 1 angiotensin 2 receptor) is associated with better endothelial function than that in patients treated with calcium channels or beta receptor blockers [31,34].…”
Section: Discussionsupporting
confidence: 91%
“…There appears to be selective targeting of the tissular ACE population linked to endothelial dysfunction by the lipophilic enalapril. This is in accordance with findings correlating vascular ACE inhibition (measured by changes in angiotensin peptide levels) [32] or vascular ACE expression (determined by genetic polymorphism) [33] with endothelial function. Moreover, the inhibition of ACE (and type 1 angiotensin 2 receptor) is associated with better endothelial function than that in patients treated with calcium channels or beta receptor blockers [31,34].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have reported associations between ACE gene polymorphisms (insertion/deletion) and cardiovascular diseases, including endothelial dysfunction, atherosclerosis, and heart failure [ 14 , 15 , 16 ]. The ACE I/D polymorphism has been linked to plasma ACE activity [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We observed that GJD-HD had the largest decrease in SBP and DBP after six weeks of treatment. Angiotensin II and endothelin-1 are the main vasoconstrictors in hypertension pathogenesis [24][25][26]. Moreover, numerous studies found that increased Ang II and ET-1 activated NF-κB signaling pathway [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%